ナンキョク クイーンモードランド オキ ノ カイヒョウ ノ ヒョウリュウ トクセイ - 宮川, 卓也; ミヤカワ, タクヤ; 大島, 慶一郎; オオシマ, ケイイチロウ; Miyakawa, Takuya; Ohshima, Kay I. (1997)
P(論文) 1992年2月20日昭和基地沖流氷域の氷盤に設置されたアルゴスブイから, クイーンモードランド沖の海氷の漂流特性を調べた。ブイの漂流は変動しながらも漂流方向はほとんど西向きで, 東経39度(2月20日)から東経14度(4月10日)での西向きの平均漂流速度は約20cm/sであった。特に3月の中旬リーセルラルセン半島を越えてから東経16度に達するまでの間に大きな漂流速度を持っていた。同様の海域において, 68枚のNOAA・AVHRR画像を用い, 特徴的な氷盤や割れ目を追跡するという手法で海氷の漂流ベクトル場を求めた。漂流ベクトル場は, 沿岸域ではおおむね西向きであるが, グンネルス海嶺の東では北向きの漂流も見られ, 全体的に海底地形とよく対応する分布になっていた。アルゴスブイ及びAVHRR画像による結果はともに, この海域での海氷の漂流は海流に強く影響されることを示唆している。 Characteristics of sea ice drift off Queen Maud Land are described on the basis of the Argos buoy deployed on the ice floe in the pack ice region off Syowa Station on February 20,1992. The drift of the buoy is consistently westward with some variability. Averaged velocity of westward drift is about 20cm/s in the region from 39°E (February 20) to 14°E (April 10). The drift velocity becomes especially large west of the Riiser-Larsen Peninsula. Drift vectors of sea ice off Queen Maud Land are obtained from 68 NOAA AVHRR images. In general, the drift vectors approximately follow the bottom contours : they are mostly westward in the coastal region, northward in the east of Gunnerus Ridge. Both the buoy and AVHRR analyses suggest that the sea ice drift is considerably influenced by the ocean current. departmental bulletin paper